2013
DOI: 10.1017/s0021223713000162
|View full text |Cite
|
Sign up to set email alerts
|

Statutory Sentencing Reform in Israel: Exploring the Sentencing Law of 2012

Abstract: In 2012 the Knesset approved a new sentencing law. Israel thus became the latest jurisdiction to introduce statutory directions for courts to follow in sentencing. The approach of the United States to structuring judicial discretion often entails the use of a sentencing grid with presumptive sentencing ranges. In contrast, the Sentencing Act of Israel reflects a less prescriptive method: it provides guidance by words rather than numbers. Retributivism is clearly identified as the penal philosophy underpinning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Such results had already materialized in jurisdictions that had adopted similar policies in other countries (Gazal-Ayal & Lowenstein Lazar, 2011). For example, a preliminary examination of the effect of the law on illegal entry into Israel indicated that the proportionality principle has been used to justify an increase in the severity of sentences (Roberts & Gazal-Ayal, 2013). In a similar vein, Klein (2016) noted that the in the United States, discretion in sentencing (The Sentencing Reform Act of 1984 (led not only to significantly harsher federal sentencing compared with state sentencing, but also increased sentencing disparity between Blacks and Whites.…”
Section: Discussionmentioning
confidence: 99%
“…Such results had already materialized in jurisdictions that had adopted similar policies in other countries (Gazal-Ayal & Lowenstein Lazar, 2011). For example, a preliminary examination of the effect of the law on illegal entry into Israel indicated that the proportionality principle has been used to justify an increase in the severity of sentences (Roberts & Gazal-Ayal, 2013). In a similar vein, Klein (2016) noted that the in the United States, discretion in sentencing (The Sentencing Reform Act of 1984 (led not only to significantly harsher federal sentencing compared with state sentencing, but also increased sentencing disparity between Blacks and Whites.…”
Section: Discussionmentioning
confidence: 99%
“…This policy implemented an increased use of supervision laws for sex and violent offenders and electronic monitoring as a parole condition (Efodi, 2014;Rosenfeld and Noah, 2021;Shoham et al, 2015). In regard to sentencing, following a major legal reform in 2012, Israeli sentencing law adopted a retributive penal philosophy and promulgated proportionality as the main ('guiding') sentencing principle (Roberts and Gazal-Ayal, 2013). The law allowed a departure from the offence-based proportionate sentencing range for rehabilitation (as mitigation) and for public protection (as aggravation) and gave criminal history only limited weight (Roberts and Gazal-Ayal, 2013;von Hirsch, 2017).…”
Section: Contextmentioning
confidence: 99%
“…Scholars have also found that boundary-work—whether boundary-making or boundary-spanning—may involve transformations of time and space to construct physical, symbolic, emotional or symbolic boundaries between social actors (Glimmerveen et al, 2020; Lamont and Molnár, 2002; Stjerne et al, 2019; Stephenson et al, 2020). Temporal understandings and norms may have opposing or competing interpretations by different professionals.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…In the determinate sentencing regime (e.g., United Kingdom, Canada, and Israel, for most offenses), punishment should be proportionate to desert (von Hirsch, 1976). The sentences imposed by the court reflect mainly proportionality of the seriousness of the offense committed by the offender and the degree of his or her culpability (see Roberts & gazal-Ayal, 2013). The impact of preventive or rehabilitative factors, unrelated to either the seriousness of the crime or offender culpability, is generally limited by a retributive limiting range, if there is one (American Law Institute, 2011;Morris, 1974;von Hirsch & Ashworth, 2005).…”
Section: Retributive Analysis Of the "Catch-22" Problem The Magnitude Of The Problemmentioning
confidence: 99%